CLINICAL CASE OF TUBERCULOUS SCLEROSIS WITH HEART DAMAGE IN NEONATAL PRACTICE - Ульяна Васильевна Михайлова; Ирина Владимировна Болгова; Елена Александровна Кондратьева; Юрий Иванович Ровда; Людмила Викторовна Абрамова; Елена Юрьевна Гуменная; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (The Publishing House Medicine and Enlightenment, 2023)
Tuberous sclerosis is a genetically determined disease from the group of phacomatoses, with a wide range of clinical manifestations, accompanied by the development of multiple benign tumors in various organs, including the brain, eyes, skin, heart, kidneys, liver, lungs, gastrointestinal tract, endocrine and bone systems. Heart damage in tuberous sclerosis includes rhabdomyomas. Rhabdomyomas are tumor-like nodular formations that occur due to the improper formation of embryonic tissue complexes. The overwhelming majority of children (50-80%) with tuberous sclerosis and rhabdomyomas of the heart, documented at birth, do not have clinical manifestations from the heart. Sometimes, tumors, gradually progressing and increasing in size, disrupt the functions of organs, sometimes leading to fatal consequences. As an example, a clinical case of rhabdomyoma in a newborn child is given.